An Inventory of Community College Short Term Contract Training Programs in the US - Miller, Michael T. (Journal of Education and Training, 2022)
Community colleges play an important role in assisting local business and industry by providing a variety of training programs for employees, including short-term programs. These contract training programs often receive public subsidies as an economic development incentive, and despite their popularity, relatively little is known about their structure, frequency of offerings, and challenges that face them. The purpose for conducting the current study was to profile and inventory these community college contract training offices. A survey was administered to a sample of 250 contract training administrators. Findings include a description of who these administrators report to, the experiences that prepared them for their positions, the typical number of programs they offer each year, how they recruit business participation, and the challenges they report facing the most frequently. These findings are important to policy makers, administrators, and scholars as they create a baseline understanding of how these programs are embedded in and represent their colleges.